Inactivating hepatitis C virus in donor lungs using light therapies during normothermic ex vivo lung perfusion - Marcos Galasso (Nature Portfolio, 2019)
Organs from donors with transmissible viral infections, such as hepatitis C virus (HCV), are not offered for transplantation due to a high risk of transmission. Here, Galasso et al. develop a method for treatment of HCV-infected human donor lungs that is safe and prevents HCV transmission in the pig model.